Psychological safety and primary care physicians’ well-being, work conditions and guideline adherence behavior: a cross-sectional study in China - Wenhua Wang; Jinnan Zhang; Rebecca Mitchell; Stephen Nicholas; Elizabeth Maitland; Jiao Lu; Xiaodong Liu (Global Health Action)
Background Health system reform initiatives have generated high-demand and created uncertain, complex practice environments, impacting the well-being, work conditions, and behavior of primary care professionals. Psychological safety is increasingly important to organizational success, particularly in highly complex work environments. Yet, few studies have examined its application among primary care professionals. Objectives To examine the impact of psychological safety on the well-being, work conditions and guideline adherence behavior of primary care physicians (PCPs) in Community Health Centres (CHCs) in urban China. Methods A total of 224 PCPs from 38 CHCs in four Chinese cities were recruited using convenience sampling. Research assistants conducted questionnaire surveys. Well-being was assessed through measures of depression, work-family conflict and work exhaustion, work conditions were defined by measures of professional commitment and self-directed learning, and guideline adherence behavior was measured through compliance with clinical guidelines and the provision of preventive care. Two-level hierarchical linear models were developed to analyze the impact of psychological safety. Results Psychological safety was negatively associated with depression, work-family conflict, and work exhaustion. Psychological safety was positively associated with professional commitment and self-directed learning and also greater adherence to clinical guidelines and the increased provision of preventive care. Conclusions This study in China confirms that a psychologically safe work environment in primary care is positively associated with improved PCPs’ well-being, enhanced professional commitment, and better adherence to clinical guidelines and preventive care provision. Given that psychological safety may be embedded in national culture, further studies should develop context-based, culturally and organizationally appropriate interventions.